Deep learning for personalized healthcare services - Chatterjee, Jyotir Moy; Chatterjee, Jyotir Moy; Hedayati, Hadi; Jain, Mohit; Jain, Vishal (Intelligent Biomedical Data Analysis ,, 2021)
This book uncovers the stakes and possibilities involved in realising personalised healthcare services through efficient and effective deep learning algorithms, enabling the healthcare industry to develop meaningful and cost-effective services. This requires effective understanding, application and amalgamation of deep learning with several other computing technologies, such as machine learning, data mining, and natural language processing.